The Use of Arkas Application: A Discourse on Solutions to Achieve Transparency and Accountability in the Management of School Operational Assistance Funds - Muhammad Ilham; Basrul A. Majid (Al-Fikru: Jurnal Ilmiah, 2023)
School Operational Assistance funds are one form of education financing from the government. School Operational Assistance funds require transparent and accountable management. This study seeks to analysis the application of the school activity and budget plan to the accountability and transparency of school operational assistance funds management at SMA N 4 Lhokseumawe. This study employs a qualitative approach with a descriptive survey design. Using the ARKAS application, it is intended to evaluate the effectiveness, accountability, and transparency of school operational assistance fund administration at SMA N 4 Lhokseumawe. Observation, interviews, and documentation were used to collect data. The results of this study show that the effectiveness of school accountability is achieved through a series of stages, including strategic planning through the results of deliberations; implementation refers to priority programs based on the school vision; monitoring and reporting openly to the program coordinator. In addition, school operational assistance financial accountability was achieved through the synergy of information disclosure and community cooperation. The effectiveness of the distribution funds was also achieved by referring to the needs of students and guided by the national education standards.